Exposure of Canadian electronic waste dismantlers to flame retardants. (August 2019) - Nguyen, Linh V.; Diamond, Miriam L.; Venier, Marta; Stubbings, William A.; Romanak, Kevin; Bajard, Lola; Melymuk, Lisa; Jantunen, Liisa M.; Arrandale, Victoria H.
Abstract: Exposure of e-waste workers to eight halogenated and five organophosphate ester flame retardant chemicals (FRs) was studied at a Canadian e-waste dismantling facility. FR concentrations were measured in air and dust samples collected at a central location and at four work benches over five-24 hour periods spanning two weeks. The highest concentrations in air from workbenches were of BDE-209 (median 156 ng m −3 ), followed by Tris(2-chloroethyl) phosphate (TCEP, median 59 ng m −3 ). Dust concentrations at the workbenches were higher than those measured at the central location, consistent with the release of contaminated dust during dismantling. Dust concentrations from the workbenches were also dominated by BDE-209 (median 96, 300 ng g −1 ), followed by Triphenyl phosphate (TPhP, median 47, 000 ng g −1 ). Most FRs were in coarse particles 5.6–18 μm diameter and 30% were in respirable particles (< 3 μm). Exposure estimates indicated that dust ingestion accounted for 63% of total FR exposure; inhalation and dermal absorption contributed 35 and 2%, respectively. Some air and dust concentrations as well as some estimated exposures in this formal facility in a high-income country exceeded those from informal e-waste facilities located in low and middle income countries. Although there is demonstrated toxicity of some FRs, FR exposure in the e-waste industry has received minimal attention and occupational limits do not exist for most FRs. Highlights: Some exposures to FRs were higher in this formal facility than in informal facilities. BDE-209 had highest air and dust concentrations, followed by organophosphate esters. 30% of total airborne FR concentrations were in respirable particles < 3 μm. Dust ingestion accounted for >60% of total FR exposure. Few occupational limits exist for FR exposure in Canadian e-waste sector.